1992
DOI: 10.1161/01.cir.85.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure control by the renin-angiotensin system in normotensive subjects. Assessment by angiotensin converting enzyme and renin inhibition.

Abstract: The lack of blood pressure effects of renin inhibition in contrast to angiotensin converting enzyme inhibition suggests that the renin-angiotensin system does not contribute significantly to blood pressure control in normotensive, sodium-replete subjects. The hypotensive activity of angiotensin converting enzyme inhibitors may result from additional hormonal effects, for example, inhibition of bradykinin degradation and/or subsequent increases of vasodilating prostaglandins or endothelium-derived relaxing fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 55 publications
1
15
0
Order By: Relevance
“…Although it is not universally accepted, ACE inhibitors do cause a small fall in blood pressure in salt replete volunteers (Kiowski et al, 1992). In this present study, there were considerable reductions in blood pressure despite a low dose of enalapril.…”
Section: Discussionsupporting
confidence: 40%
“…Although it is not universally accepted, ACE inhibitors do cause a small fall in blood pressure in salt replete volunteers (Kiowski et al, 1992). In this present study, there were considerable reductions in blood pressure despite a low dose of enalapril.…”
Section: Discussionsupporting
confidence: 40%
“…3,4 Briefly, forearm blood flow was measured by strain-gauge plethysmography after intra-arterial infusion of increasing doses of the endothelium-dependent vasodilators bradykinin (infusion rates: 100, 200, and 400 ng/min) and acetylcholine (infusion rates: 7.5, 15, and 30 g/min) 16,17 and of the endothelium-independent vasodilator sodium nitroprusside (infusion rates: 0.8, 1.6, and 3.2 g/min). 18 Drugs sequence was randomized to avoid bias related to the order of infusion.…”
Section: Endothelial Function Studiesmentioning
confidence: 99%
“…Recent inhibitor, thus indicating a role of NO in the late phase of studies strongly indicate that kinin participates in the control bradykinin-induced hypotension (Rees et al, 1990). However, of blood pressure (BP) (Kiowski et al, 1992; Cachofeiro et similar results were not obtained by O'Shaughnessy et al al., 1992;Pellacani et al, 1992). It has been suggested that (1992), thus questioning the role of NO as a mediator in the hypotensive effect of bradykinin is mediated through the bradykinin-induced hypotension.…”
Section: Introductionmentioning
confidence: 96%